HRM in the tourism industry: inferences from research - Martins-Rodrigues, M.; Rosa, L.; Sousa, M.; Barberi, L.; Godoy, T. (Handbook of Research on Multidisciplinary Approaches to Entrepreneurship, Innovation, and ICTs, 2021)
This chapter aims to analyze the research from the last 20 years about human resources management in the tourism industry. The research question is: What are the contributions of the international publications on human resources management and tourism in the Web of Science and Scopus databases in the last two decades? In order to accomplish this goal, the research methodology will be a literature survey using the Scopus and WoS databases. To develop this research, first, it will be performed a literature review on HRM as strategic value, and also on the multiple perspectives of the concept of tourism. Moreover, it will be made state of the art on human resources management in the tourism industry. Furthermore, the results of the literature survey are presented. The main findings show that there is still a need for more production about human resources management in the tourism industry, which was based on the importance of one segment to the other, as well as the infinite possibilities of incremental actions that allow a mutual benefit between these two fields.